2021
DOI: 10.1088/2058-8585/ac1fd7
|View full text |Cite
|
Sign up to set email alerts
|

Sinter-free inkjet-printed PEDOT:PSS/WO3/PEDOT:PSS flexible valency change memory

Abstract: With the rapid proliferation of consumer electronics in our day to day lives, there is an ever increasing demand for flexible electronic devices which are low cost, easy to fabricate and deliver reliable performance. In this work, we report fabrication of symmetric poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)/WO 3 /PEDOT:PSS memory cells by inkjet printing on transparent, flexible polyethylene naphthalate (PEN) substrates. The cells show resistive switching behavior with two stable resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In this study, we consider three of the most commonly used conduction mechanisms for oxide materials: space-charge-limited conduction (SCLC), Poole–Frenkel, and Schottky emission. , As defects, specifically oxygen vacancies embedded in the Hf 0.5 Zr 0.5 O 2 – δ lattice, act as shallow traps, trapping and de-trapping provide an easy conduction pathway. Taking this into account, the first mechanism considered for fitting the HRS I – V curves is the space-charge-limited (SCLC) model, which is commonly used to explain the carrier migration process involved in resistive switching , and is strongly related to characteristic parameters of charge traps. The current density for SCLC can be written as follows …”
Section: Resultsmentioning
confidence: 99%
“…In this study, we consider three of the most commonly used conduction mechanisms for oxide materials: space-charge-limited conduction (SCLC), Poole–Frenkel, and Schottky emission. , As defects, specifically oxygen vacancies embedded in the Hf 0.5 Zr 0.5 O 2 – δ lattice, act as shallow traps, trapping and de-trapping provide an easy conduction pathway. Taking this into account, the first mechanism considered for fitting the HRS I – V curves is the space-charge-limited (SCLC) model, which is commonly used to explain the carrier migration process involved in resistive switching , and is strongly related to characteristic parameters of charge traps. The current density for SCLC can be written as follows …”
Section: Resultsmentioning
confidence: 99%
“…Due to the nature of the mechanism, high ON-OFF ratios have been achieved for the ZnO-based conductive bridge RAMs obtained by Sputtering, atomic layer deposition (ALD), pulsed laser deposition (PLD) and Sol-gel [21]. In an effort to explore how ZnO responds as the active material in a printed valency change ReRAM, we investigate the key performance parameters of these memory cells and report improved retention and endurance as compared to previously reported memories based on WO 3 [22].…”
Section: Introductionmentioning
confidence: 88%
“…Different oxide materials and semiconductors such as WO 3 [22], TiO 2 [23], ZrO [24], and CuO [25] have been used to fabricate ReRAM cells, and several studies have shown the attractive potential of oxide-based active layers for the memory. The design of printable and flexible cells make them remarkably interesting due to their low cost, safe use, high scalability, and unique electrical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…This includes analog-type memristors to emulate biological synapses and neurons [16,17] and digital-type memristors for data storage applications. [18] Most of these devices are fabricated using advanced manufacturing methods, such as atomic layer deposition and magnetron sputtering, [16][17][18][19] but recently also printing of memristors is becoming more and more popular [20][21][22][23][24][25][26][27][28][29] Regarding printed electronics, digital printing technologies, such as electrohydrodynamic jet-, aerosol-, and inkjet-printing, are of particular interest due to their additive, material efficient, non-contact, and maskless fabrication capabilities. [30,31] Recent works on printed memristors mostly focus on digital-type memristors with filamentary type of resistive switching suitable for flexible or printed memory applications.…”
Section: Introductionmentioning
confidence: 99%